1999
DOI: 10.1021/cr9800255
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Energetics, and Dynamics of the Nucleic Acid Base Pairs:  NonempiricalAb InitioCalculations

Abstract: ContentsI. Introduction 3247 II. Calculations 3249 II.1. Interaction Energy 3249 II.2. Correlation Energy 3250 II.3. Density Functional Theory 3251 II.4. Vibrational Frequencies 3251 II.5. Gas-Phase Thermodynamic Characteristics of Nucleic Acid (NA) Base Pairs 3252 III. Structure and Properties of Isolated NA Bases 3252 III.1. Tautomeric Equilibria of Bases 3252 III.2. Protonization Energies of Bases 3253 III.3. Electrostatic Potential around NA Bases 3254 III.4. Polarizability 3255 III.5. Gas-Phase Electron A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
866
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 997 publications
(922 citation statements)
references
References 248 publications
53
866
1
2
Order By: Relevance
“…This is justified not only by economy Additionally, these tetramers belong to the less polar steps. On the contrary the d(GpG) is known [11,12] as the most polar system among all ten possible dinucleotide steps, what also is confirmed by mean values of dipole moment collected in Table 1. Besides, much lower values of SCF contribution are noticed in this case if compared to previously described set of dinucleotides.…”
Section: Linear Relationships Of Intermolecular Interactionssupporting
confidence: 65%
See 2 more Smart Citations
“…This is justified not only by economy Additionally, these tetramers belong to the less polar steps. On the contrary the d(GpG) is known [11,12] as the most polar system among all ten possible dinucleotide steps, what also is confirmed by mean values of dipole moment collected in Table 1. Besides, much lower values of SCF contribution are noticed in this case if compared to previously described set of dinucleotides.…”
Section: Linear Relationships Of Intermolecular Interactionssupporting
confidence: 65%
“…A special example of system involving complicated interplay between many forces of different character [9][10][11] is found in the case of stabilization of polynucleotide chains. Many contributions are important for DNA involving contacts of its constituents as nucleobases, sugar moieties, phosphate backbones, surrounding water molecules, counter ions and diversity of ligands potentially present in solutions at physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a for conventional numbering of the ring atoms) [34,35]. MPI mass spectra of pure uracil clusters have previously been measured using 274 nm ns-timescale laser pulses but no information on fragment ions was reported [36].…”
Section: Uracil Clusters and Uracil-adenine Clustersmentioning
confidence: 99%
“…The basis set used is 6-31G**(0.2), which corresponds to the standard 6-31G** basis set where the Gaussian ␣ d -exponent of the d-polarization functions on the heavy atoms C, N, and O is equal to 0.8, with an additional ␣ d -exponent equal to 0.2. It has indeed been shown that this extended description of the d-polarization functions allows a more accurate description of cation-interactions (21,22). 1 The interaction energy ⌬E MP2 is calculated as the sum of the Hartree-Fock energy ⌬E HF and a correlation energy contribution ⌬E COR , evaluated here in Equation 1 as the second order term of the Møller-Plesset perturbation expansion.…”
Section: Structural Dataset Of Protein-ligandmentioning
confidence: 99%